Pelatihan Guru SD dalam Mengembangkan Pembelajaran Matematika Kontekstual Berbasis Wisata Edukasi melalui Math City Map di Taman Beregam, Musi Rawas - Drajat Friansah; Sukasno Sukasno; Yufitri Yanto; Zaqi Andre Alfian; Sindy Anjelina (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2025)
This community service aimed to improve elementary teachers’ competence in designing contextual mathematics learning using Math City Map at Taman Beregam, Musi Rawas. The two-day training covered preparation, implementation, and mentoring stages. Results indicated an increase in teachers’ understanding of contextual learning from 26% to 82%. Eleven out of fifteen participants (73.3%) successfully created contextual tasks integrating measurement, geometry, and ratio concepts with real park objects. Interview analysis revealed six main themes: learning transformation, technological innovation, adaptation challenges, implementation plans, institutional support, and teacher professionalism. The training effectively enhanced teachers’ innovative capacity in developing contextual, technology-supported mathematics learning.